GOOD CORPORATE GOVERNANCE PADA PERBANKAN SYARIAH DI INDONESIA - Tsaqif Fadhlilhaq; Muhammad Rafi N; Rizky Wahyu Pranata; Muhammad Nizham Ramadhika H; Renny Oktafia (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Islamic banking has become an integral part of the Indonesian financial system, with significant growth in recent years. However, to ensure continuity and public trust, implementing Good Corporate Governance (GCG) is important. This article presents an analysis of the challenges and opportunities in implementing GCG in sharia banking in Indonesia. Challenges such as the complexity of organizational structures and limited human resources are being overcome with technological innovation and increased awareness and education. Existing opportunities, such as inter-institutional collaboration, can strengthen the capacity of sharia banking in implementing strong GCG practices. Therefore, this article not only identifies the obstacles faced by sharia banking, but also highlights strategies to improve the implementation of GCG, which in turn will support the growth and stability of the sharia banking industry in Indonesia.